2020
DOI: 10.1088/2058-8585/ab71e3
|View full text |Cite
|
Sign up to set email alerts
|

Wide-range work function tuning in gold surfaces modified with fluorobenzenethiols toward application to organic thin-film transistors

Abstract: Surface properties of Au electrodes modified by benzenethiol derivatives with a fluorine atom(s) have been methodically researched based on measurements of the work function and the contact angles. Benzenethiol derivatives with a fluorine atom(s) at ortho, meta, and/or para position were used for modification in this work. The measured work function was in a relatively wide range between 4.24-6.02 eV. The work function change from a bare Au surface was explained on the principle of dipole moments obtained by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Many reports have demonstrated that using a different contact metal [ 64 ] or otherwise modifying φ C through chemical means like dipolar SAMs [ 117,151 ] can improve the contact resistance in organic transistors, ostensibly due to a reduction in the relevant injection‐barrier height. This is at least part of the explanation that is given for the often‐excellent contact resistance improvement of p‐channel bottom‐contact organic TFTs, which utilized PFBT and other fluorinated SAMs, [ 154,174 ] including the experimental instances reviewed in the previous section. [ 30,33,34 ] This has thus motivated investigations into other thiol molecules capable of forming dipolar SAMs on the metal contacts with some particular emphasis on those with a larger number of fluorine atoms to induce a work‐function shift to higher energies beyond that obtained with PFBT.…”
Section: Present Challenges For Realizing a Contact Resistance Of 1 ω...mentioning
confidence: 99%
“…Many reports have demonstrated that using a different contact metal [ 64 ] or otherwise modifying φ C through chemical means like dipolar SAMs [ 117,151 ] can improve the contact resistance in organic transistors, ostensibly due to a reduction in the relevant injection‐barrier height. This is at least part of the explanation that is given for the often‐excellent contact resistance improvement of p‐channel bottom‐contact organic TFTs, which utilized PFBT and other fluorinated SAMs, [ 154,174 ] including the experimental instances reviewed in the previous section. [ 30,33,34 ] This has thus motivated investigations into other thiol molecules capable of forming dipolar SAMs on the metal contacts with some particular emphasis on those with a larger number of fluorine atoms to induce a work‐function shift to higher energies beyond that obtained with PFBT.…”
Section: Present Challenges For Realizing a Contact Resistance Of 1 ω...mentioning
confidence: 99%
“…The modification of metal surfaces utilizing organic compounds containing sulfur has been widely studied for decades. , Organic compounds chemically react on a metal surface and form a monolayer on it. This monolayer is useful for improving the performance of electronic devices , and fabricating nanosized materials and devices. The properties of a monolayer, such as density, coverage, defects, homogeneity, and assembly order, depend on the preparation process and can affect the characteristics of an electronic device that is used. Therefore, a thorough characterization of monolayers is required for their application in electronic devices .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Organic compounds chemically react on a metal surface and form a monolayer on it. This monolayer is useful for improving the performance of electronic devices 3,4 and fabricating nanosized materials and devices. 5−7 The properties of a monolayer, such as density, coverage, defects, homogeneity, and assembly order, depend on the preparation process and can affect the characteristics of an electronic device that is used.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Meanwhile, it is proven that the fluorine substituted NHCs have the capacity to increase the π-accepting ability from metal π-back bonding and hence change the electron density in metal surfaces. 31 In light of work by Kitamura et al using fluorine substituted thiol derivatives for electrode modification, 32 here we designed and synthesized a fluorine-substituted N-heterocyclic carbene (F-NHC) as electrode modifier to explore its effect on contact resistance in OFETs. In comparison to devices without F-NHC modifications, the carrier mobility of C8-BTBT and TIPS-Pen transistors with F-NHC modified gold electrodes reached 0.17 and 0.14 cm 2 V −1 s −1 , presenting significant improvement factors of 33 and 9, respectively.…”
Section: Introductionmentioning
confidence: 99%